HUBUNGAN KUANTITATIF STRUKTUR-AKTIVITAS ANTIMALARIA SENYAWA TURUNAN QUINOLINE-PYRAZOLOPYRIDINE - Mardianingrum, Richa (STIKes Bakti Tunas Husada, 2018)
Indonesia one of the high endemic countries of malarial disease, while the use of drugs that are still resistant can spread parasites and cause death. The purpose of this study was to find new antimalarial drug candidates through the Quantitative-Structure and Activity Relationship (QSAR) of quinolin-pyrazolopiridine derivative compounds. QSAR is an important part of drug design in an effort to obtain a new drug with greater activity, higher effectiveness, toxicity or the smallest possible side effects and greater comfort. In reviewing QSAR, it can use the Hansch approach parameter in the form of electronic, lipophilic and steric. From the modeling of 20 quinolin-pyrazolopiridine derivatives the best QSAR equation: Log EC50 = 134,137 + 5,067 (LogP) + 0,036 (ETot) – 5,539 (Polarisibility) – 0,218 (Dipol) + 0,309 (BM) + 0,004 (MTI) + 0,028 (CMA) + 0,227 (VMol) n = 20 r = 0,984 r2 = 0,968 SE = 0,661824